Implementing International Soft Law Commitments on Wastewater Management in Vietnam: Evaluation and Lessons Learned - Vu, Hai Dang; Pham Thi, Gam; Nguyen Thi, Xuan Son; Le Thi, Anh Dao; Nguyen, Tien Vinh (Universitas Negeri Semarang, 2025)
The main global commitments on the prevention of land-based pollution in general and on the prevention of land-based wastewater pollution in particular are found in soft law instruments. This article examines international soft law commitments on the prevention, reduction and elimination of land-based wastewater pollution and how Vietnam has implemented them in its national law. From this analysis, a number of lessons would be extracted for other countries in terms of implementing international soft law commitments.